Modeling-Based Response-Guided DAA Therapy for Chronic Hepatitis C to Identify Individuals for Shortening Treatment Duration. (22nd March 2022) - Goyal, Ashish; Churkin, Alex; Barash, Danny; Cotler, Scott J; Shlomai, Amir; Etzion, Ohad; Dahari, Harel
Abstract: Shortening duration of direct-acting antiviral therapy for chronic hepatitis C could provide cost savings, reduce medication exposure, and foster adherence and treatment completion in special populations. The current analysis indicates that measuring hepatitis C virus at baseline and on days 7 and 14 of therapy can identify patients for shortening therapy duration.